Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Adjoining Grave markers of Rosa Langston Watkins (7/5/1901-4/20/1973) and Amos J. Watkins (8/31/1896-12/6/1946) Chattanooga Memorial Park